2018
DOI: 10.5114/aoms.2018.79008
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nebivolol on doxorubicin-induced cardiotoxicity in rats

Abstract: IntroductionThe cardiotoxicity of doxorubicin is incompletely understood. We investigated the prophylactic effect of nebivolol on doxorubicin-induced cardiac toxicity.Material and methodsThirty rats were divided into a control group, doxorubicin-treated group and nebivolol + doxorubicin-treated group. The specimens were examined using H + E and Masson’s trichrome, caspase 3, endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS) and tumor necrosis factor factor-α (TNF-α). The mean are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
2
21
1
2
Order By: Relevance
“…Earlier preclinical studies have proven nebivolol to be beneficial in the reduction of cardiotoxicity. 10,11 However, such a benefit was not observed in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…Earlier preclinical studies have proven nebivolol to be beneficial in the reduction of cardiotoxicity. 10,11 However, such a benefit was not observed in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…Inflammatory processes are activated by the migration of leukocytes, inflammatory chemokines and cytokines to the site of tissue injury. 33 TNF-α is activated before leukocytic infiltration occurs especially in the site of local inflammation. 34 Previous studies have demonstrated that oxidative stress aggravates inflammation in I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…These findings in our study were in agreement with those reported by previous studies; which used NEB and demonstrated its anti-inflammatory effects. 14,33 Previous studies have demonstrated that increased oxidative stress causes an increase in the expression of apoptosis markers in groups with I-induced and I/R induced injury. 34 In our study, we demonstrated the apoptotic damage induced by I and I/R-induced injury in the ovarian cell by using the TUNEL assay.…”
Section: Discussionmentioning
confidence: 99%
“…Densitometry analysis was performed using the Image J software (NIH Image, Bethesda, USA). GAPDH was used as the control [23].…”
Section: Western Blot Analysismentioning
confidence: 99%